Good corporate governance practices in family businesses in the coach building sector of Duitama, Colombia - Báez-Roa, María del Pilar; Puentes-Montañez, Gloria Acened; Sosa, Viviana Catalina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of the research was to identify good corporate governance practices in family companies in the auto body industry, located in the department of Boyacá, Colombia. The study had a qualitative approach, with descriptive research and non-experimental field design, using the semi-structured interview as the information gathering technique. The sample corresponded to 10 family businesses, where their owners were interviewed. The findings showed that most companies are in the first generation, and have not considered the formal application of good corporate governance practices. However, it is observed that there is an intuitive presence of these practices, an aspect that is reflected in: the low level of family conflicts, taking advantage of the advantages of being a family business and applying participatory management, which has led to the sustainability of the long-term companies.